SMOOTHING THE TRANSITION TO BUSINESS ANALYTICS - MITRA L. DEVKOTA; ERIC B. HOWINGTON (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
With the growing volume and variety of data, knowledge of business analytics is essential for organizations to make data-driven decisions that can significantly improve performance, efficiency, and competitiveness of the business. As the popularity of analytics increases, so will the need for people who have knowledge and skills to convert big data into actionable insight that managers and other decision makers need to improve decision making in the real business world. Colleges and universities are increasing Analytics-related offerings at both graduate and undergraduate levels. The instructors tasked with teaching these new course offerings are generally the same instructors that are relied upon for business statistics education. This paper attempts to provide some recommendations regarding classroom teaching, available software choices, and course materials based on our experience in teaching the business analytics course